Studi Dinamika Populasi Udang Putih (Penaeus merguiensis, deMan 1888) di Perairan Sungai Bela, Kabupaten Indragiri Hilir: Pendugaan Beberapa Parameter Kunci - Harahap, Syaiful Ramadhan; Yusapri, Andi; Rachman B, Arief; Nurhasan, Nurhasan; Fahlifi SF, M Riza; Ihwan, Khairul; Yulianti, Yulianti (SIMBIOSA, 2025)
This study examined the population dynamics of Banana Prawns (Penaeus merguiensis) in the waters of Sungai Bela, focusing on sex ratio, length-weight relationship, and natural recruitment patterns. The results show a dominance of female individuals in the population with a sex ratio of 1:1.19 (male : female), which may affect reproduction processes and population sustainability. The length-weight relationship demonstrated a negative allometric growth pattern, in which body mass grew faster than body length. Shrimp recruitment patterns show seasonal fluctuations, with recruitment peaks in July and October, which are influenced by temperature, salinity, and food availability. This study highlights the importance of continuous monitoring of the sex ratio and recruitment patterns, as well as management based on environmental factors, to support the sustainability of P. merguiensis populations. Sustainable management, including habitat conservation and catch control, is essential for maintaining ecosystem balance and ensuring the sustainability of shrimp stocks in the future.